Transformation of UML Diagrams based on their Overlapping: An Algorithmic Approach - Rehman, M.; Ullah, S.; Siddique, A. (The Nucleus, 2022)
Modeling methods in general and Unified Modeling Language (UML) in particular, have gained trust in software developer communities. UML diagrams are profoundly utilized by software developers to build, model and visualize the working of the software. While the comprehension of the UML models can introduce ambiguities in the software. As there is no specification on how these models should be analyzed. Therefore, these models sometimes convey inconsistent semantics in the software systems. So, there must be some automated procedure in which these models be transformed into one another, to remove analyst-introduced ambiguities. For this purpose, the conversion between UML diagrams is a necessity. This paper aims at solving this inconsistency gap between UML diagrams by providing a novel approach to conversion between UML models. In this paper, we have proposed novel techniques to convert 1) UML Use-Case diagram into UML Communication diagram. 2) UML Communication diagram into UML Component diagram. The said approach is validated using two case studies.